The impact of serious games with humanoid robots on mild cognitive impairment older adults. Issue 145 (January 2021) - Manca, Marco; Paternò, Fabio; Santoro, Carmen; Zedda, Eleonora; Braschi, Chiara; Franco, Roberta; Sale, Alessandro
Highlights: The design of a serious game to help older adults train their memory with versions for two different devices (tablet and humanoid robot). A study with fourteen older adults with mild cognitive impairments using the game through the two devices in a training programme. An analysis of the impact of the rich multimodal feedback provided by the humanoid robot version of the application on the older adults. A discussion of more general implications that can be derived from the presented study. Abstract: The number of Mild Cognitive Impairment (MCI) older adults is increasing; thus, it becomes more and more important to provide them with support to avoid, or at least slow down, their cognitive decline. To this end, interactive serious games can play an important role. So far, most of them have been deployed through tablets, which represent a cost-effective solution, yet offering only limited possibilities for truly engaging such users in a multimodal manner. However, emerging humanoid robots, through their physical embodiment and human-like attributes, including facial expressions and body language, may open up new possibilities in more effectively engaging MCI older adults during repetitive cognitive training. We present a study aiming to better understand the impact of humanoid robots in supporting serious games for such users. In particular, we investigate how seniors with Mild Cognitive Impairments relate to and perceive serious games accessed through humanoid robots, as part of a training programme aimed to improve their cognitive status. For this purpose, two versions of a music-based memory game have been designed by a multi-disciplinary team, one for humanoid robots and one for tablets. We report on its use during a between-subject study that involved MCI seniors, and discuss their experience. The results show that the robot was received with more enthusiasm by the older adults, thus improving their level of engagement.